Improving dynamic knowledge movements with a knowledge movements with a knowledge-based framework during conceptual design of a green building project - Pourzolfaghar, Zohreh; Ibrahim, Rahinah; Abdullah, Rusli; Adam, Nor Mariah; Abang Ali, Abang Abdullah (IGI Global, 2013)
Many researchers believe that tacitness of knowledge contributes to incomplete knowledge flow. In this article, the authors focus on obtaining the required mechanical and electrical tacit knowledge for architectural conceptual design purpose by observing activities of a design team involved in a green building project. The authors used the case study research methodology to demonstrate how the authors could utilize Macmillan's conceptual design framework and integrate it with the structure of repertory grid technique to obtain a framework of knowledge-based conceptual design for a green building project. The contribution of this study is developing a technique for capturing tacit knowledge during the conceptual design process that leads to an improvement in knowledge movements during the architectural conceptual design stage.